2012
DOI: 10.1200/jco.2011.35.6345
|View full text |Cite
|
Sign up to set email alerts
|

ROS1 Rearrangements Define a Unique Molecular Class of Lung Cancers

Abstract: A B S T R A C T PurposeChromosomal rearrangements involving the ROS1 receptor tyrosine kinase gene have recently been described in a subset of non-small-cell lung cancers (NSCLCs). Because little is known about these tumors, we examined the clinical characteristics and treatment outcomes of patients with NSCLC with ROS1 rearrangement. Patients and MethodsUsing a ROS1 fluorescent in situ hybridization (FISH) assay, we screened 1,073 patients with NSCLC and correlated ROS1 rearrangement status with clinical char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

46
1,124
5
20

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 1,444 publications
(1,226 citation statements)
references
References 22 publications
46
1,124
5
20
Order By: Relevance
“…30,37 However, this association has not been consistently observed across studies. 34 Other clinical characteristics, such as younger age, female sex, and non-Asian ethnicity, have been associated with ROS1 rearrangement in isolated studies only.…”
Section: Expert Consensus Opinionmentioning
confidence: 96%
See 4 more Smart Citations
“…30,37 However, this association has not been consistently observed across studies. 34 Other clinical characteristics, such as younger age, female sex, and non-Asian ethnicity, have been associated with ROS1 rearrangement in isolated studies only.…”
Section: Expert Consensus Opinionmentioning
confidence: 96%
“…This recommendation is evidence based and supported by 9 studies, 30e38 6 of which informed on the association between ROS1 rearrangement and patient or tumor characteristics 30,31,34e37 and consisted of 1 prospective cohort study (PCS), 35 1 prospective-retrospective cohort study (PRCS), 31 and 4 retrospective cohort studies (RCSs). 30,34,36,37 The 3 remaining studies assessed clinical outcomes of patients treated with the ROS1-targeted therapy crizotinib 32,33,38 and included 1 nonrandomized clinical trial 33 and 3 RCSs. 32,38 All included studies were assessed for quality and none were found to have methodologic flaws that would raise concerns about the studies' findings (SDC Table 6).…”
Section: Strong Recommendationmentioning
confidence: 99%
See 3 more Smart Citations